STRATEGI PROMOSI PHOTOMATICSID DENGAN MENGGUNAKKAN APLIKASI MEDIA SOSIAL TIKTOK (STUDI KASUS PADA PHOTOMATICSID) - Doni Yusuf Aristiono (2022)
Photomaticsid is a business entity that only uses the TikTok social media application as a promotional medium. However, until now, its sales are increasing and still exist. This research was conducted to learn more about the promotion strategy of Photomaticsid using the social media TikTok. This research is qualitative research using the case study research method. Researchers used case studies to find out what promotional activities were. Data collection techniques were carried out through In-depth Interviews and Documentation. The data obtained were then analyzed using making explanation. This study's results show that all elements of the Marketing Mix or Marketing Mix are in every TikTok video made by Photomaticsid, namely, product, price, place, people, promotion, process, and physical evidence. In the process of making the Photomaticsid promotional strategy on TikTok social media, it is also following the concept of Symbolic Interaction Theory, namely the Generalized other, which is shown in how Photomaticsid determines promotional strategies related to TikTok videos. Also, all TikTok Photomaticsid videos are under the concept of role taking in Interaction Theory Symbolic.